Understanding Asnaf’s Sustainability through Effective Distributive Performance: A Conceptual Assessment - Al Haq, M Ashraf; Abd. Wahab, Norazlina (2017)
Zakat is receiving due position in Islamic welfare management studies for the last few years as the global situation in terms of unpredictability is on the rise.Interestingly and positively, both collection and distribution of zakat is increasing year after year yet still something is missing. The effectiveness of distribution of Zakat in terms of timely delivery or quality options of asnaf sustainability is still a big question. The issue of effective delivery requires a performance measurement, which may invite the zakat organisations to look into the possibility of incorporating a scorecard approach in evaluating the achievements thus far.This study attempts to look into asnaf sustainability as a measuring tool and an evaluation criterion for understanding the zakat’s institutional performance while keeping the demographic profile as a balancing option in assessing the relationship. The study is in elementary stage for which data analysis and further recommendation is still forthcoming.It will thus highlight the issues related to autonomous zakat body versus non-autonomous zakat bodies’ priority and problem resolving tactics in addressing the asnaf’s sustainability.The study put forward a conceptual assessment comprising of potential evaluating criterion variables for assessing asnaf sustainability and their relationship with performance of zakat distribution system. The outcomes of the study will enable theorists and policy makers in Islamic societies as well as in Islamic countries to devise effective approaches towards a promising zakat distribution system and thereby achieve the objectives of welfare.